Hydrogen production through photoreforming processes over Cu2O/TiO2 composite materials: A mini-review. (30th October 2020) - Muscetta, Marica; Andreozzi, Roberto; Clarizia, Laura; Di Somma, Ilaria; Marotta, Raffaele
Abstract: Cu2 O is a promising low-cost semiconductor exhibiting a narrow band gap. The combination of p-type Cu2 O with n-type TiO2 results in a p-n heterojunction highly beneficial to photocatalytic processes, due to the resulting capability of (i) absorbing visible light irradiation and (ii) promoting charge carrier separation. An intense scientific activity has been recorded in the field of H2 generation through water photosplitting and organic photoreforming over Cu2 O/TiO2 -based composites. This literature survey aims at clarifying conflicting information on the preparation, characterization, and use of Cu2 O/TiO2 composites for H2 evolution. Detailed information on analytical techniques devoted to uniquely identifying Cu2 O has been provided. Preparation method, effect of pH, effect of sacrificial agent, chemical stability of Cu2 O/TiO2 composites, and reaction mechanisms have been critically discussed. The highest efficiency values obtained over Cu2 O/TiO2 photocatalysts have been reported. A solid groundwork on which developing new effective and low-cost materials for H2 generation has been provided. Graphical abstract: Image 1 Highlights: First comprehensive literature survey on Cu2 O/TiO2 photocatalysts for H2 generation. Comparison of preparation methods, organics and pH used, and efficiencies recorded. Clear information on analytical techniques uniquely identifying Cu2 O in Cu2 O/TiO2 . Insight into reaction mechanisms for H2 evolution over Cu2 O/TiO2 photocatalysts.